ДЕРЖАВНА ПОЛІТИКА У СФЕРІ РОЗВИТКУ СОЦІАЛЬНО ВІДПОВІДАЛЬНОГО БІЗНЕСУ: ЗАРУБІЖНИЙ ДОСВІД ДЛЯ УКРАЇНИ - Butyrskyi, Oleksandr (Zhytomyr Ivan Franko State University, 2025)
The article is devoted to current issues in the field of corporate social responsibility (CSR) as a factor in ensuring business activity and its development in Ukraine during times of crisis, as well as the role of the state in supporting enterprises and organizations that actively implement CSR principles. The main manifestations of social responsibility are outlined. To achieve the research objective, a comparative method was applied, based on the analysis of statistical data to assess the implementation of European practices in Ukrainian businesses and the standards approved by key programmatic documents of the European Union. The use of analysis, synthesis, comparison, extrapolation, and generalization methods contributed to reaching the research goal and drawing conclusions about key trends and directions of socially responsible practices in the Ukrainian business environment. As a result of critical analysis and synthesis of existing approaches to the essence of social responsibility, the article defines its substantive characteristics, core components, and levels of implementation, drawing on international experience. The level of social responsibility of Ukrainian enterprises is examined, and ways to enhance their business activity through the formation of a positive corporate image, improved reputation, and strong relationships with clients and partners are identified. Special attention is given to the development of social responsibility during states of emergency, particularly during wartime. The article proposes recommendations for the implementation of the European model of corporate social responsibility. The practical value of the research findings lies in the identification of key trends in the development of social responsibility in the domestic business sector, which align with global tendencies in their focus on community needs. It is also noted that despite obvious deterrents, businesses in Ukraine have not abandoned CSR practices during wartime; on the contrary, they have become more oriented toward addressing the needs of society, the state, and local communities.